2021
DOI: 10.2217/fon-2020-0490
|View full text |Cite
|
Sign up to set email alerts
|

Metaplastic Breast Cancer: an Old Histotype but a Current Therapeutic Problem

Abstract: Metaplastic breast cancer (MPBC) is a rare and aggressive tumor type in great need of satisfactory therapies. Although most cases of MPBC are ‘triple negative’, they are nonetheless related to worse outcomes compared with other triple-negative invasive tumors. MPBC presents high levels of genetic and molecular heterogeneity, suggesting that novel targeted therapies can be exploited. Overexpression of PD-L1 and high levels of tumor-infiltrating lymphocytes have also been observed in these tumors, suggesting a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this study, the type of surgery had nothing to do with the prognosis of MBC patients, which is consistent with previously reported results ( Corso et al, 2021 ). However, different studies suggest that surgical removal of the tumor has a great benefit if combined with radiation therapy, and an improvement of overall survival has been observed for both mastectomy and lumpectomy patients ( Gadaleta-Caldarola et al, 2021 ). Li et al showed that even elderly women (≥60 years old) can benefit from radiotherapy ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the type of surgery had nothing to do with the prognosis of MBC patients, which is consistent with previously reported results ( Corso et al, 2021 ). However, different studies suggest that surgical removal of the tumor has a great benefit if combined with radiation therapy, and an improvement of overall survival has been observed for both mastectomy and lumpectomy patients ( Gadaleta-Caldarola et al, 2021 ). Li et al showed that even elderly women (≥60 years old) can benefit from radiotherapy ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other therapeutic options with well-studied and established targets should be considered, such as, for example, platinum based treatment, immunotherapy, and chemotherapy in MpBC [75] [107,108]. Gadaleta-Caldarola et al suggested the use of liquid biopsy as a useful tool to predict prognosis, to evaluate the effectiveness of targeted therapy and even the detection of the development of resistance [109].…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…Now recently conducted studies have shown that long term outcomes improved with neo-adjuvant chemotherapy and combined chemotherapy and radiotherapy (Li et al, 2019;Wang et al, 2019). The immunological studies have demonstrated a potential role of immunotherapy as it has high levels of PD-L1 and tumor infilterating T lymphocytes (Gadaleta-Caldarola et al, 2021).…”
Section: Introductionmentioning
confidence: 99%